H. Pylori Infection in Iraqi patients with ischemic heart diseases - AL-Obeidy, Eman Sh.; Saeed, Basil. N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cardiovascular diseases are among the most common cause of death in Developed countries. In addition to traditional risk factors for cardiovascular disease, nowadays, accumulating evidence indicates that a variety of infectious agents may contribute to pathogenesis of ischemic heart disease. Patients and methods: 125 patients (25 females and 100 males) attending the department of cardiology, Baghdad, teaching hospital over the period December 2008- June 2009were enrolled. Their age range  between (39-75 years) compared with 50 healthy individuation (Age & sex matched). The sera were tested for H. pylori antibodies using enzyme linked immunosorbent assay (ELISA).Results: 80% of patients showed the anti-H. Pylori IgGs (P < 0.05). But there were no significant association between risk factors & H. pylori infection (P > 0.05).Conclusions: These findings raise the possibility that exposure to H. pylori may lead to increased risk of coronary artery disease independent of other risk factors.